Supporting Information - Adonis Lupulescu (10498406) (2025)
Section S.1: SSFP under MAS in the presence of second-rank anisotropies: Liouvillians and steady-state signals in the presence and absence of rotor synchronization. Section S.2: Rotor echoes under MAS-SSFP and miss-synchronization: Numerical simulations